Endothelial dysfunction, platelet hyperactivity, hypertension, and the metabolic syndrome: molecular insights and combating strategies - Das, Diptimayee; Shruthi, Nagainallur Ravichandran; Banerjee, Antara; Jothimani, Ganesan; Duttaroy, Asim K.; Pathak, Surajit (Frontiers in Nutrition, 2023)
Metabolic syndrome (MetS) is a multifaceted condition that increases the possibility of developing atherosclerotic cardiovascular disease. MetS includes obesity, hypertension, dyslipidemia, hyperglycemia, endothelial dysfunction, and platelet hyperactivity. There is a concerning rise in the occurrence and frequency of MetS globally. The rising incidence and severity of MetS need a proactive, multipronged strategy for identifying and treating those affected. For many MetS patients, achieving recommended goals for healthy fat intake, blood pressure control, and blood glucose management may require a combination of medicine therapy, lifestyles, nutraceuticals, and others. However, it is essential to note that lifestyle modification should be the first-line therapy for MetS. In addition, MetS requires pharmacological, nutraceutical, or other interventions. This review aimed to bring together the etiology, molecular mechanisms, and dietary strategies to combat hypertension, endothelial dysfunction, and platelet dysfunction in individuals with MetS.